"Mapping" Smart Cities. Issue 2 (3rd April 2019) - Loo, Becky P. Y.; Tang, Winnie S. M.
ABSTRACT: Smart cities are designed to use data to optimize resources, maintain sustainability, and improve people's quality of life. While many urban technologies are employed to make cities "smart, " one constellation of technologies has been less examined in the academic literature—digital maps and the spatial data infrastructure. This paper is an attempt to systematically review the functions and evolution of digital maps and the spatial data infrastructure, with examples from Asia and beyond, in supporting and making smart cities possible. Based on the conceptual framework and empirical case studies, four major research directions of smart mapping are identified to better support smart city initiatives.